1997
DOI: 10.1023/a:1022426910111
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Formation of nitric oxide, and endothelium-derived relaxing factor, can be inhibited by administration of N-nitro-L-arginine methylesther (L-NAME). In the present study, the activity of the sympathoadrenal system in rats with blood pressure (BP) elevation induced by L-NAME was investigated. L-NAME was administered in a dose of 50 mg/kg, i.p. every 12 h for 4 days. Blood samples were collected via chronically inserted arterial catheters in conscious, freely moving rats at rest and during immobilization stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In line with the fact that L-NAME upregulates NE release and metabolism, the bioactive compounds and some sub-fractions that decreased BP may have acted as adrenergic antagonists or they had the ability to decrease interstitial NE concentration. Decreased heart rates induced by L-NAME were consistent with previous studies (Fellet et al, 2003;Kvetnansky et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with the fact that L-NAME upregulates NE release and metabolism, the bioactive compounds and some sub-fractions that decreased BP may have acted as adrenergic antagonists or they had the ability to decrease interstitial NE concentration. Decreased heart rates induced by L-NAME were consistent with previous studies (Fellet et al, 2003;Kvetnansky et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…From this proposal it is possible that decreased HR induced by L-NAME maybe as a result of activation of baroreceptor afferents by increased BP which resulted in activation of the parasympathetic vagal innervations of the heart. Considering the second suggestion, a study done by Kvetnansky et al (1997) revealed significant elevation of NE metabolites in L-NAME treated animals in spite of unchanged levels of plasma NE thus suggesting that L-NAME increases release, turnover, reuptake and metabolism of NE in the sympathoneural system. In line with this suggestion, Saeed, Khan, & Shabbir (2012) found that the magnitude of interstitial NE can increase far greater than that in plasma and thus they suggested that NE movement into the circulation decreases with baroreceptor unloading.…”
Section: Discussionmentioning
confidence: 99%
“…The adrenergic activation by L-NAME leads to the release of adrenaline and Noradrenaline, eventually exerting positive inotropic and chronotropic effect on the myocardium causing elevated blood pressure. It also acts by increasing Renin and Ang-II levels in the renal system, thereby augmenting plasma aldosterone and retaining Na + and water [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, the absence of NO can heighten the vasoconstriction phenomenon by increasing the levels of vasoconstrictors like NA and Ang II. This point could be explained by a prolonged blockade of nitric oxide synthesis that causes arterial hypertension (associated with an activation of the sympathoadrenal system) [ 142 ]. Nitric oxide is not only involved in functional antagonism of NA, but also affects the production of NA.…”
Section: Interaction Of Nitric Oxide With Other Systemsmentioning
confidence: 99%